Anti-tumor activity of sulfated polysaccharides from Sargassum fusiforme - Miao Yu; Yubin Ji; Zheng Qi; Di Cui; Guosong Xin; Bing Wang; Yue Cao; Dandan Wang (Elsevier, 2017)
In this study, our purpose is to discover the correlation between polysaccharides sulfated structure and anti-tumor activity. Sulfated polysaccharide from Sargassum fusiforme were synthesized with the chlorosulfonic acid pyridine method. The inhibitory effect of Sargassum fusiforme polysaccharides and the application of MTT assay before and after chemical modification on the proliferation of hepatocellular carcinoma HepG-2 cells in vitro were studied. Sulfated polysaccharide from sargassum fusiforme DS is 0.803. The modified polysaccharide has certain inhibitory effect on HepG-2 cells, and its inhibition on the cells growth has improved compared with the original SFPs. The sulfated polysaccharide from Sargassum fusiforme has the ability to enhance anti-tumor activities. Keywords: Sargassum fusiforme polysaccharide, Sulfation, MTT method, Anti-tumor